Rancang Bangun Monitoring Beban Listrik Dengan Daya 450va Berdasarkan Urutan Prioritas Menggunakan Arduino Nodemcu Esp8266 - Yogi Setiawan; Yuliarman Saragih; Dian Budhi Santoso (Jurnal Ilmiah Wahana Pendidikan, 2021)
One of the basic human needs in the household is electrical energy and the need for power used in the electrical load in the household is very limited, depending on the electrical power capacity owned by the homeowner in accordance with the value purchased, needed electrical energy in the household Exceeds the capacity installed power. The purpose of this study is to study the design and electrical control system used to prevent sudden tripping. The method in this study uses a load control system design method with 450VA power based on Arduino NodeMCU ESP8266. This arduino NodeMCU ESP8266 is designed to create a system that can connect the flow of electricity that remains connected and uninterrupted on the MCB (Miniature Circuit Breaker) due to the large amount of electric current discharged. The results of the design of this tool can be used to read large currents used then compare with the available electric current capacity. If the current exceeds the capacity in this design with a maximum current of 450VA, the system will begin to reduce the load from priority 4. If the current still exceeds the maximum limit, the system will turn off one by one the load in order of priority. For this tool it has been declared successful and is running as desired.